Prostate‐to‐bladder cross‐sensitization in a model of zymosan‐induced chronic pelvic pain syndrome in rats. Issue 4 (19th January 2021) - Aydogdu, Ozgu; Gocun, Pinar Uyar; Aronsson, Patrik; Carlsson, Thomas; Winder, Michael
Abstract: Background: The aim of the present study was to investigate the effects of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) on bladder function and pathophysiology. Methods: To create a model for CPPS, rats were intraprostatically injected with zymosan or saline, serving as control. Metabolic cage experiments were performed 7, 14, or 21 days after zymosan injection and after 14 days in the control group. Thereafter, cystometry was performed in which simulated micturition cycles were induced by saline infusion and contractile responses to the cholinergic agonist methacholine and the purinergic agonist ATP were measured. Following cystometry, the prostate and urinary bladder were excised and assessed histopathologically for possible inflammatory changes. Results: Metabolic cage data revealed a significantly increased urinary frequency in zymosan treated rats. Likewise, the volume per micturition was significantly lower in all CPPS groups compared to controls. Cystometry showed a significant increase in the number of nonvoiding contractions, longer voiding time, and a trend towards lower compliance in CPPS rats compared to controls. Induction of CPPS led to significantly reduced cholinergic and purinergic contractile responses. Histopathological analysis demonstrated prostatic inflammation in all CPPS groups, in particular in later stage groups. Both the extent and grade of bladder inflammation were significantly higher in CPPS groups compared to controls. Conclusions: The current findings demonstrate a potential prostate‐to‐bladder cross‐sensitization leading to symptoms of bladder overactivity and signs of bladder inflammation. Future clinical studies are required to verify the outcomes of the current study and enable advancement of patient care.